Dispersive ionic liquid microextraction of aluminium from environmental water samples by effervescent generation of carbon dioxide. Issue 8 (20th June 2016) - Naeemullah,; Tuzen, Mustafa; Kazi, Tasneem Gul; Citak, Demirhan
ABSTRACT: A green effervescent in-situ generation of CO2 -tablet-induced dispersive ionic liquid microextraction (DILME) method has been first time used for the preconcentration and determination of trace levels of aluminium [Al(III)] in real water samples by graphite furnace atomic absorption spectrometry (GFAAS). In the present approach, 1-methyl-3-octylimidazolium hexafluorophosphate [OMIM][PF6 ] was dispersed in an aqueous medium by the effervescent reaction of CO2 -tablet to increase phase transfer ratio, which significantly improve the extraction recovery of Al(III) complex with 1-(2-pyridylazo)-2-naphthol, into extraction solvent. Limit of detection and enrichment factor were found to be 0.045 µg L −1 and 42.4, respectively. Validation of the developed method was carried out to determined Al(III) in a certified reference material (SLRS-4 riverine water) and the results were found to be in good agreement with the certified value. The relative standard deviation was found to be 4.3%. The developed method was applied to different water samples.